DIE SLEUTEL VAN JERUSALEM - Visser, J.A. (Scientia Militaria - South African Journal of Military Studies, 2012)
The article below, dealing with the role of the South African Artillery in the capture of Nebi Samwll (8 km northwest of Jerusalem) during World War 2, is but a short extract from a much more comprehensive work on the SA artillery that is being undertaken by the Military Information Bureau, Pretoria. One of the burning questions that still remains unanswered is: what happened to the historic canon, on which the Key of Jerusalem was engraved, that played such a vital part in this particular campaign? If anyone should have information on the whereabouts of these canon, he is requested to contact the Military Information Bureau at Private Bag X 289, Pretoria 0001 (telephone no 28-1731 X 554), as soon as possible.